Communism and Democracy : History, debates and potentials - Makin-Waite, Mike (Book collections on Project MUSE., 2017)
On the centenary of the Russian Revolution of 1917, Mike Makin-Waite surveys the history of the communist movement, tracking its origins in the Enlightenment, and through nineteenth-century socialism to the emergence of Marxism and beyond. As we emerge from the long winter of neoliberalism, and the search is on for ideas that can help shape a contemporary popular socialism, some of the questions that have preoccupied socialist thinkers throughout left history are once more being debated. Should the left press for reform and work through the state or should it focus on protest and a critique of the whole system? Is it possible to expand the liberal idea of democracy to include economic democracy? Which alliances require too great a compromise and which can help secure future change? Arguments on questions such as these have been raging since the mid-nineteenth century, and were the basis of the split between Social Democrats and Communists in the aftermath of the First World War. Mike Makin-Waite believes that revisiting these debates can help us to avoid some of the mistakes made in the past, and find new solutions to some of these age-old concerns. His argument is that the democratic and liberal counter-currents that have always existed within the communist movement have much to offer the left project today. This unorthodox account therefore tracks an alternative history that includes nineteenth-century revisionists such as Karl Kautsky, Menshevik opponents of Bolshevik oppression in 1917, Popular Front critiques of sectarianism in the 1930s, communist support for 1968's Prague Spring, and the turn to Gramsci and Eurocommunism in the 1970s. The aim of Communism and Democracy: history, debates and potentials is to recover some of the hard-won insights of the critical communist tradition, in the belief that they can still be of service to the twenty-first-century left.